Human triacylglycerol-rich lipoprotein subfractions as substrates for lipoprotein lipase. - Fisher, R; Coppack, S; Humphreys, S; Gibbons, G; Frayn, K (1995)
In order to test the hypothesis that lipoprotein lipase (LPL) acts preferentially on larger lipoprotein particles, we determined the susceptibility of triacylglycerol-rich lipoprotein (TRL) subfractions to hydrolysis by LPL in vitro. Chylomicrons (Sf > 400), very low density lipoproteins (VLDL)1 (Sf 60-400) and VLDL2 (Sf 20-60) were isolated from six subjects with a range of plasma-triacylglycerol (TAG) concentrations following an overnight fast and for up to 6 h after the consumption of a mixed meal (41% fat). The percent of TRL-TAG hydrolysed by LPL in subfractions isolated following overnight fast was VLDL1 > VLDL2 (46.8 +/- 10.2 vs. 25.9 +/- 7.4%, P = 0.006) and 3 h after the meal it was chylomicrons > VLDL1 > VLDL2 (81.0 +/- 12.6 vs. 52.8 +/- 10.2 vs. 27.7 +/- 6.2%, chylomicrons vs. VLDL1 and VLDL1 vs. VLDL2, both P < or = 0.005). The percent of VLDL1-TAG hydrolysed increased both within and between subjects as VLDL1-TAG concentrations increased. This relationship could be explained by the positive correlation observed between VLDL1-TAG and VLDL1-TAG:apolipoprotein B. In conclusion, increasing the size and TAG content of a lipoprotein particle increases its susceptibility to hydrolysis by LPL.